Supervision by the Regional Police Inspectorate Regarding Online Public Complaints Considering Regional Police Performance to Improve Professionalism and Legal Certainty (Study at the Regional Police Inspectorate of the West Kalimantan Regional Police) - Shandy Christyan Sulu; KMS Herman (Indonesian Journal Publisher, 2026)
This study strives to analyze the supervision by the Regional Supervision Inspectorate of online public complaints regarding the Indonesian National Police's performance in order to enhance legal certainty and professionalism. This study uses a statutory and conceptual approach in conjunction with a normative juridical research method. The 1945 Constitution of the Republic of Indonesia, Law Number 2 of 2002 concerning the Indonesian National Police, Law Number 25 of 2009 concerning Public Services, and Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems are just a few of the legal provisions that the statutory approach seeks to analyze. Meanwhile, the conceptual approach aims to explore legal concepts related to internal supervision, the professionalism of law enforcement officers, and the law enforcement system's legal stability. The findings show that the Regional Supervision Inspectorate's internal supervision system is essential for investigating public complaints about police officers' performance by receiving, confirming, reviewing, and assessing public reports. The public can submit reports more easily and complaints are handled with greater accountability and transparency when an online public complaints system is used. However, there are still a number of challenges in implementing this monitoring, such as a lack of human resources, complex investigation procedures, and the optimization of information technology in managing public complaints. Therefore, strengthening the internal oversight system is necessary to enhance the professionalism of police officers and ensure legal certainty for the public.